Plant Protein Amyloid Fibrils for Multifunctional Sustainable Materials. (12th January 2023) - Li, Ting; Zhou, Jiangtao; Peydayesh, Mohammad; Yao, Yang; Bagnani, Massimo; Kutzli, Ines; Chen, Zhengxing; Wang, Li; Mezzenga, Raffaele
Abstract: Artificial functional materials based on amyloid fibrils are proven to be a promising strategy toward functional materials. However, scaling‐up applications present sustainability concerns, as animal proteins are the main sources for fabricating amyloid fibrils. Plant‐protein‐based amyloid fibrils, a more sustainable alternative to animal proteins, are attracting increasing interests as building blocks in functional materials. Herein, 11 different sources from a wide range of plants are evaluated, and a comprehensive analysis of seven species of plant proteins, including kidney bean, black bean, cowpea, mung bean, chickpea, lentil, and pumpkin seed, with an excellent ability to form fibrils, is presented. A universal strategy for a diversity of plant protein extraction and fibrillization is applied. Flexible fibrils with a persistence length of ≈100 nm and rigid fibrils of several micrometers are discovered in 7S/8S and 11S subunits dominated protein, respectively. Structural evolution toward the β‐sheet content on these proteinaceous assemblies is characterized by thioflavin T (ThT) intensity, circular dichroism (CD) spectra, attenuated total reflectance‐Fourier transform infrared (ATR‐FTIR) spectra, and typical wide angle X‐ray scattering (WAXS) spectra. Finally, their multifunctional applications are further explored and proven that these sustainable protein amyloids demonstrate excellent performance in renewable and degradable bioplastics, and in water purification membranes for heavy metal removal. Abstract : This study evaluates eleven different sources from a wide range of plants, and narrows down the study to seven species of plant proteins from which excellent amyloid fibrils can be generated. Furthermore, the possible applications of these plant based amyloid fibrils in multifunctional materials, such as the hydrogels, biodegradable plastics, and water purification membranes are demonstrated in this work.